A randomized double-blind study of testosterone replacement therapy or placebo in testicular cancer survivors with mild Leydig cell insufficiency (Einstein-intervention) - Bandak, Mikkel; Jørgensen, Niels; Juul, Anders; Lauritsen, Jakob; Kreiberg, Michael; Oturai, Peter Sandor; Helge, Jørn Wulff; Daugaard, Gedske (BMC cancer, 2017)
Elevated serum levels of luteinizing hormone and slightly decreased serum levels of testosterone (mild Leydig cell insufficiency) is a common hormonal disturbance in testicular cancer (TC) survivors. A number of studies have shown that low serum levels of testosterone is associated with low grade inflammation and increased risk of metabolic syndrome. However, so far, no studies have evaluated whether testosterone substitution improves metabolic dysfunction in TC survivors with mild Leydig cell insufficiency. This is a single-center, randomized, double-blind, placebo-controlled study, designed to evaluate the effect of testosterone replacement therapy in TC survivors with mild Leydig cell insufficiency. Seventy subjects will be randomized to receive either testosterone replacement therapy or placebo. The subjects will be invited for an information meeting where informed consent will be obtained. Afterwards, a 52-weeks treatment period begins in which study participants will receive a daily dose of transdermal testosterone or placebo. Dose adjustment will be made three times during the initial 8 weeks of the study to a maximal daily dose of 40 mg of testosterone in the intervention arm. Evaluation of primary and secondary endpoints will be performed at baseline, 26 weeks post-randomization, at the end of treatment (52 weeks) and 3 months after completion of treatment (week 64). This study is the first to investigate the effect of testosterone substitution in testicular cancer survivors with mild Leydig cell insufficiency. If positive, it may change the clinical handling of testicular cancer survivors with borderline low levels of testosterone. ClinicalTrials.gov : NCT02991209 (November 25, 2016).